Effectiveness of Realistic Mathematics Education in Improving Grade 7 Students’ Learning Outcomes in a Rural Zambian Secondary School - Musonda, Allan; Mubila, Leonard; Mulenga, Justina (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the effectiveness of the Realistic Mathematics Education approach in improving mathematics learning outcomes of Grade 7 students in a rural Zambian secondary school. Methodology: A quasi-experimental design with a one-group pretest–posttest model was employed. The participants consisted of 26 Grade 7 students selected from a rural public secondary school in Zambia. Data were collected through mathematics achievement tests, classroom observation sheets, and student response questionnaires. Descriptive statistical analysis was used to evaluate learning effectiveness based on learning outcomes, student activities, and student responses. Main Findings: The results indicate that the implementation of Realistic Mathematics Education led to a significant improvement in students’ mathematics achievement, with most students achieving the minimum mastery criterion and demonstrating a high normalized gain score. In addition, students showed active participation during learning activities and expressed positive responses toward the Realistic Mathematics Education -based instruction. Novelty/Originality of this study: These findings suggest that Realistic Mathematics Education is an effective instructional approach for enhancing mathematics learning in rural secondary school contexts in Zambia.